2011
DOI: 10.1021/jp107099z
|View full text |Cite
|
Sign up to set email alerts
|

Observable Temperature-Dependent Compaction−Decompaction of Cationic Polythiophene in the Presence of Iodide

Abstract: Investigation on compaction and decompaction of polymers is very important since it is a fundamental problem in polymer physics. With the aids of atomic force microscope (AFM) and dynamic light scattering (DLS) measurements in this contribution, the temperature-dependent compaction/decompaction transition process of water-soluble cationic polythiophene (PT) was investigated in the presence of KI. The above process is characterized by the red-to-yellow color change and fluorescence recovery and is reversible du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…The AFM study indicated that the thickness of free polymer is ca 120 nm at both 25 and 55 °C, but the thickness decreases to ca 60 nm in the presence of KI at 25 °C. From these data it was claimed that at 25 °C in the presence of KI the polymer adopts a less conjugated, nonplanar conformation …”
Section: Water‐soluble Cptmentioning
confidence: 99%
See 1 more Smart Citation
“…The AFM study indicated that the thickness of free polymer is ca 120 nm at both 25 and 55 °C, but the thickness decreases to ca 60 nm in the presence of KI at 25 °C. From these data it was claimed that at 25 °C in the presence of KI the polymer adopts a less conjugated, nonplanar conformation …”
Section: Water‐soluble Cptmentioning
confidence: 99%
“…(A) Schematic of polythiophene conformational change when exposed to ligands or varying surroundings and (B) the observable temperature‐dependent compaction/de‐compaction of polythiophene in the presence of KI. (Reproduced from Wang et al )…”
Section: Water‐soluble Cptmentioning
confidence: 99%
“…In recent years, colorimetric sensing has drawn increasing attention to decrease experimental cost, simplify the sensing process and determine the target concentration visually. This method has been used for many kinds of target detection with satisfactory results . Significant advances have been made in the development of colorimetric sensors for Ag + detection, however, there is still a need to set up a convenient colorimetric method for Ag + that has a wide detection range, low determination limit, as well as high selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Conformational changes can be promoted by changing temperature, pH, ionic strength, cations, anions, surfactants, nucleic acids, proteins, etc. [2][3][4][5][6][7][8][9][10] A detailed study of the optical transitions of a water-soluble PT induced by surfactant addition was performed by Knaapila and coworkers. 8,9 The optical transitions are correlated with the changes in the type of CPE-surfactant aggregate formed in solution.…”
Section: Introductionmentioning
confidence: 99%